Factorization by Regrouping

In factorization by regrouping sometimes the terms of the given expression need to be arranged in suitable groups in such a way that all the groups have a common factor. After this arrangement factorization becomes easy.


Method of factoring terms:

Step 1: Arrange the terms of the given expression in groups in such a way that all the groups have a common factor.

Step 2: Factorize each group.

Step 3: Take out the factor which is common to each group.


Solved problems on factorization by regrouping the terms:

1. How to factorize the following expressions?



(i) a2 + bc + ab + ac

Solution:

The expression is a2 + bc + ab + ac

By suitably rearranging the terms, we have;

= a2 + ab + ac + bc

= a(a + b) + c(a + b)

= (a + b) (a + c).


(ii) ax2 + by2 + bx2 + ay2

Solution:

The expression is ax2 + by2 + bx2 + ay2

By suitably rearranging the terms, we have;

= ax2 + ay2 + bx2 + by2

= a(x2 + y2) + b(x2 + y2)

= (x2 + y2) (a + b).

2. Factor grouping the algebraic expressions:

(i) xy - pq + qy - px

Solution: 

xy - pq + qy - px 

By suitably rearranging the terms, we have; 

= (xy - px) + (qy - pq) 

= x (y - p) + q (y - p) 

= (y - p) (x + q). 

Therefore by factoring expressions we get (y - p) (x + q).


(ii) ab(x2 + y2) + xy(a2 + b2).

Solution:

ab(x2 + y2) + xy(a2 + b2)

By suitably rearranging the terms, we have;

= abx2 + aby2 + a2xy + b2xy

= (abx2 + a2xy) + (aby2 + bxy)

= ax(bx + ay) + by(ay + bx) 

= ax(bx + ay) + by(bx + ay) 

= (bx + ay) (ax + by).

Therefore by factoring expressions we get (bx + ay) (ax + by)





8th Grade Math Practice

From Factorization by Regrouping to HOME PAGE


New! Comments

Have your say about what you just read! Leave me a comment in the box below. Ask a Question or Answer a Question.



Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.